PENERAPAN STRATEGI PEMBELAJARAN MURDER (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW) DALAM PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP PATRA MANDIRI01 PALEMBANG - Anita Fatimatus Suriyah; Karoma Karoma; Muhammad Fauzi (Jurnal PAI Raden Fatah, 2022)
This study aims to: (1) Knowing the learning outcomes of grade VII students applied murder learning strategies (Mood, Understand, Recall, Digest, Expand, Review) in Islamic subjects. (2) Knowing the learning outcomes of grade VII students who are not applied murder learning strategies (Mood, Understand, Recall, Digest, Expand, Review). (3) To find out the difference in student learning outcomes between the classes applied and not applied MURDER learning strategies (Mood, Understand, Recall, Digest, Expand, Review). The type of research used is experimental research. Experimental research is research that is planned in such a way that the phenomenon can be isolated from other influences. Data collection techniques used are observation, tests, and documentation. Data analysis using test t. The results of the study stated that the learning results of grade VII 1 student of SMP Patra Mandiri 01 Palembang who use murder strategy (Mood, Understand, Recall, Digest, Expand, Review) is classified as higher than the learning outcomes of grade VII 2 students who do not use murder strategy (Mood, Understand, Recall, Digest, Expand, Review). This can be seen from the hypothetical test results using the calculation of the test "t" namely (t0 = 4,893) the magnitude of the "t" listed in the table of values t (table5%= 2.04 and table1%= 2.74) then can be known that t0 is greater than tt which is 2.04<4,893>2.74. So the proposed nil hypothesis is rejected, this means a significant improvement in learning outcomes after the MURDER strategy is implemented.